Water Management in the Era of Climatic Change Volume II - Kuriqi, Alban; Garrote, Luis (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The world faces a water crisis that is exacerbated by climate change. With just 3% of Earth's water being freshwater, much of it is inaccessible. Only 0.08% is used by humans, impacting ecosystems. This collection aims to provide solutions, knowledge, and tools for sustainable water resource management. The demand for water, particularly for agriculture, is rising, leading to competition among users. The conservation of freshwater ecosystems is vital. Climate change will further strain water resources, affecting agriculture and soil productivity. This collection of 89 papers offers insights and solutions for global stakeholders, aiding decision-makers in addressing water-related challenges in an ever-changing world.